(untitled) (International Journal of Medical and Surgical Sciences, 2015)
Spermatogenesis is a complex physiological process that involves cell proliferation, meiotic division and a final cell differentiation of post-meiotic cells into spermatozoa. During this process male germ cells also undergo a metabolic differentiation process, in which post-meiotic spermatogenic cells (spermatids) but not meiotic spermatogenic cells (spermatocytes) respond differentially to D-glucose metabolism, glucose transporters (GLUTs) distribution and utilization of non-hexose substrates, such as lactate/pyruvate or dihydroxyacetone. These differences might be explained by the requirement for a specific metabolic process to support cell differentiation or in some cases, cell viability. In addition, though glycogen is considered to be the main glucose store, in male germ cells this polymer may play a novel role in cell proliferation, acting as a new marker for apoptotic events in testicular tissue via a yet unknown mechanism. In this article, we summarize the main metabolic changes that occur during male germ differentiation, with a specific focus on metabolic sources during spermatocyte to spermatid transition. The latter considering that these cells come from the same cell linage as specialized cells, but are not isolated from their environment, describing the roles from single molecules to polymers on the viability of male germ cells.